New records of the predaceous midge genus Palpomyia from Mexico, with a new species in the Palpomyia distincta group (Diptera: Ceratopogonidae) - Huerta, Herón; Spinelli, Gustavo R. (Zootaxa, 2021)
Palpomyia auakua, a new predaceous midge in the Palpomyia distincta group, is described and illustrated from females collected with Malaise trap in a cloud forest at 1470 m. in Tlanchinol, Hidalgo, Mexico. This new species is compared with three Neotropical species, Palpomyia paulistensis Lane and P. castanea Macfie from Brazil, and P. yamana Spinelli et al. from Tierra del Fuego, and its similar Nearctic species P. jamnbacki Grogan & Wirth. Also included the first record of P. aspina Grogan & Wirth from Mexico and Guatemala, and new records of P. subaspera (Coquillett) from Veracruz and Tabasco. A key to males and females of species of Palpomyia that inhabit Mexico is also included.